1998
DOI: 10.1002/(sici)1096-9861(19980323)392:4<428::aid-cne2>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Twofold overexpression of human ?-amyloid precursor proteins in transgenic mice does not affect the neuromotor, cognitive, or neurodegenerative sequelae following experimental brain injury

Abstract: By using transgenic mice that overexpress human beta-amyloid precursor proteins (APPs) at levels twofold higher than endogenous APPs, following introduction of the human APP gene in a yeast artificial chromosome (YAC), we examined the effects of controlled cortical impact (CCI) brain injury on neuromotor/cognitive dysfunction and the development of Alzheimer's disease (AD)-like neuropathology. Neuropathological analyses included Nissl-staining and immunohistochemistry to detect APPs, beta-amyloid (Abeta), neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 62 publications
2
60
0
Order By: Relevance
“…Thus, for years the relationship between experimental TBI and brain amyloidosis has been characterized by conflicting results. Reports have shown that following controlled cortical impact (CCI), the APP-YAC mice do not develop plaques when evaluated acutely after injury (Murai et al 1998), and in PD-APP mice, CCI produces a marked ipsilateral hippocampal atrophy, almost complete CA3-CA2 cell loss and diminished Ab deposition during aging (Smith et al 1998;Nakagawa et al 1999Nakagawa et al , 2000. On the contrary, in PD-APP mice subjected to CCI brain injury, amyloid deposition is accelerated only in the presence of APO-E4 while cell loss is not influenced (Hartman et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for years the relationship between experimental TBI and brain amyloidosis has been characterized by conflicting results. Reports have shown that following controlled cortical impact (CCI), the APP-YAC mice do not develop plaques when evaluated acutely after injury (Murai et al 1998), and in PD-APP mice, CCI produces a marked ipsilateral hippocampal atrophy, almost complete CA3-CA2 cell loss and diminished Ab deposition during aging (Smith et al 1998;Nakagawa et al 1999Nakagawa et al , 2000. On the contrary, in PD-APP mice subjected to CCI brain injury, amyloid deposition is accelerated only in the presence of APO-E4 while cell loss is not influenced (Hartman et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The brains were removed, post-fixed overnight, sliced into 2-mm-thick coronal slabs, and embedded in paraffin in a frontal to occipital series of blocks, and the blocks were cut in a near serial array of 6-lm thick coronal sections. Paraffin sections were subjected to immunohistochemistry (IHC) as previously described (Murai et al 1998;Nakagawa et al 1999Nakagawa et al , 2000. Ab deposits were visualized by NAB228, Ab monoclonal antibody (mAb; Lee et al 2003).…”
Section: Histological and Immunohistochemical Analysismentioning
confidence: 99%
“…66,85,87,88 Briefly, the MWM is a circular pool 1 m in diameter that is painted white inside. 65 The water (16-18˚C) filling the pool is made opaque by adding nontoxic, watersoluble white paint.…”
Section: Assessment Of Cognitive Functionmentioning
confidence: 99%
“…The brains were fixed in 70% ethanol in 150 mmol/L NaCl, pH 7.4, or in 10% neutral buffered formalin and processed for IHC analyses using n847 and a panel of antibodies to other neurodegeneration-related proteins (see Table 2 for details on this antibody panel) as described previously. 35,36 The antibody-probed slides were developed with avidin-biotin complex (ABC) method (Vectastain ABC Kit, Vector Laboratories, Burlingame, CA) using positive and negative controls as described. 35,36 Semiquantitative analysis of n847-IR CA1 neurons was conducted by examining eight photographs of the CA1 region of each section from each case using 20X lens and a Nikon-FXA microscope.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…35,36 The antibody-probed slides were developed with avidin-biotin complex (ABC) method (Vectastain ABC Kit, Vector Laboratories, Burlingame, CA) using positive and negative controls as described. 35,36 Semiquantitative analysis of n847-IR CA1 neurons was conducted by examining eight photographs of the CA1 region of each section from each case using 20X lens and a Nikon-FXA microscope. Neurons with different n847 staining patterns were identified, counted, and statistically analyzed using analysis of variance.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%